PENAMBAHAN TEPUNG LIMBAH UDANG DALAM RANSUM BASAL TERHADAP KARKAS AYAM PEDAGING - Harahap, Anwar Efendi (Jurnal Peternakan Nusantara, 2020)
Shrimp waste has high protein to be used as broiler feed. The purpose of this study was to determine the addition of shrimp waste flour into basal ration to carcass weight, life weight, percentage of carcass and abdominal fat in broilers aged between 14 to 35 days. This study used 60 unsexing 1 day-old chicks of Cobb strains) and kept from the age of 0-13 days feed commercial rations while those aged 14-35 days were feed basal rations. A completely radomized design (CRD) was applied with four treatments and five replications consisting three chickens each. The treatments were P0 (ration + 0% shrimp waste flour), P1 (ration + 2.5% shrimp waste flour), P2 ration + 5% shrimp was flour and P3( ration + 7.5 % shrimp was flour). The results of this study indicated that the addition of shrimp waste flour up to the level of 7.5% has a very significant effect on carcass weight, carcass percentage, abdominal fat of broilers aged between 14 to 35 days. It is concluded that the addition of shrimp waste flour to the level of 7,5% into the ration has improved broiler carcass